Before Extensive Reading: Students’ Reading Attitude and Preference - Agustina Lestary (TEFLA Journal (Teaching English as Foreign Language and Applied Linguistics Journal), 2022)
This study aims to describe the students’ reading habit, attitudes towards reading English texts, and preferences on Extensive Reading. These three points are deemed essential before introducing Extensive Reading to the students in the classrooms. Students’ reading habit, attitudes and preferences will help the teachers in designing the Extensive Reading activity in their classes so that the students can still have enjoyable experience of reading while reaching the target language goals. This study is a descriptive study. Questionnaire is given to 32 university students taking Intercultural Reading course to understand the students’ view on reading. Adult Survey Reading Attitude (ASRA) is modified as questionnaire items. The result of this study shows that the students have positive attitude towards reading English text. They find reading English texts is difficult but they fully agree that reading will help them in learning English. It is also preferable for the students to choose their own texts for Extensive Reading. By understanding the students’ attitude and preference, the teachers can set Extensive Reading that fit the students’ condition